Morphological and Lexicosemantic Behaviour of Lexical Units “Golovnaya Bol', Migren', Tsefalgiya and Headache, Migraine, Cephalgia” in the Corpus Environment - Lacková, Marta (Research in Language, 2021)
The paper deals with the morphological and lexicosemantic characteristics of lexical units golovnaya bol', migren', tsefalgiya and headache, migraine, cephalgia. The research focuses on collocations, word combinations and concordances in which they appear. At the same time, we consider their grammatical relations, semantic restrictions and semantic prosody. The whole linguistic material is investigated in the framework of the text corpora Russian Web 2011 (ruTenTen11) and English Web 2015 (enTenTen15) with the help of the search tool Sketch Engine. To begin the research, the frequencies of these lexical units in individual styles are elaborated and we also look into the etymology of the studied words as these two factors influence their behaviour from the morphological and lexicological perspectives.